Juridicial Review of Corruption Crimes for Forgery of Bussiness License (Supreme Court Decision Number 44/PID.SUS-TPK/2023/PN.SBY) - Manro Manrie Sipayung (Warmadewa Press, 2024)
This research discusses the Corruption Crime case involving counterfeiting of alcoholic beverage business permits at the Surabaya District Court Number 44 /Pid.Sus-TPK/2023/PN.Sby. This research uses a normative juridical and descriptive qualitative approach to analyze related legal norms and their legal and sociological impacts. The main data was obtained from the Surabaya District Court decision and related legal regulations, while the secondary data was from legal literature and other documents. The findings of the research show that the crime of corruption is a crime against humanity which is classified as an extraordinary crime (extra ordinary crimes) where according to the author the most appropriate punishment for corruptors is extraordinary punishment (extra ordinary law). However, the judge's decision in trying the defendant was very low, one of which was the decision that the author analyzed, namely a prison sentence of 2 (two) years and 6 (six) months, with a fine of IDR 50,000,000.00 (fifty million rupiah) subsidiary 6 (six) Months of Confinement. The author conveys to improve law enforcement, the capacity of legal officers, and openness in the legal process.